Settlement agreements in Appealing, Cassation proceedings in Commercial process and at the stage of execution of judicial decisions - Verbitska, Mariana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article deals with the peculiarities of the conclusion and approval of settlement agreements in the commercial process in the audit courts. Considerable attention is paid to the order of execution of settlement agreements. The changes in the regulation of settlement agreements according to the CPC of Ukraine are analyzed, outstanding problems are outlined and the ways of their solution are proposed.